‘We've come from the gutter, we're going back to the gutter': an exploratory study of healthcare conditions in Pollsmoor prison - Busco, Victor (University of Cape Town, 2025)
In recent years, public discourse on South African prison healthcare has highlighted a significant gap in contemporary research. While existing literature have laid a foundational understanding, there remains a lack of empirical studies addressing the changing healthcare dynamics within these institutions. Prisons, often veiled from public scrutiny, present unique challenges in understanding the actual healthcare conditions without direct investigation. This study aims to fill this gap by focusing on healthcare at Pollsmoor Medium B, a unit of the well-known Pollsmoor Correctional Centre. It focuses on identifying the specific barriers inmates face in accessing healthcare services within this facility. Through extensive thematic analysis of qualitative data collected through interviews and document reviews, the research uncovers that the healthcare provisions at Pollsmoor Medium B are markedly substandard, failing to meet both national and international human rights norms. While it is unclear whether these conditions are uniformly prevalent across all prison units, the findings indicate systemic issues with management and healthcare service delivery. The study concludes with a strong recommendation for thorough reforms to ensure the health rights of inmates are protected and upheld.